Cost-benefit analysis of drought risk reduction anticipatory action in the Western Province of Zambia - Matchaya, Greenwell C.; Kasoma-Pele, Winnie; Mutenje, Munyaradzi (International Water Management Institute, 2025)
Recurrent droughts in Zambia continue to undermine agricultural production, household incomes, and food security, while increasing dependence on costly humanitarian responses. This technical report applies a cost-benefit analysis to assess the economic viability of selected drought risk reduction anticipatory actions in the Western Province of Zambia, a region highly exposed to rainfall variability and recurrent drought events. The analysis evaluates three intervention options: farmer-led small-scale irrigation, adoption of drought-tolerant crop varieties, and a combined strategy integrating irrigation, where feasible, with drought-tolerant crops on land that is non-irrigable.